The Attitudes towards English as a foreign Language: A survey to some Students at MAN 1 Batanghari - Siti Kholipah; Ahmad Syauqi Harsyah; Amri Ikhsan (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2023)
This study investigated students’ attitudes towards language and English language learning at Islamic senior high schools (Madrasah Aliyah Negeri) 1 Batanghari. This research is part of survey research. Survey study is designed to provide a quantitative or numeric description of trends, attitudes, or opinions of a population by studying a sample of that population (Creswell, 2012). The data were collected from questionnaires and focus group interviews. There were 120 students of the 2022-2023 academic year. The students showed positive attitudes as there was a 3.6684 total mean score gained by 120 students toward two variables presented. The interview findings revealed that the students' positive attitude may be caused by their motivation, instrumental and integrative. Teachers should respect and carefully investigate students' feelings, beliefs, needs, and behaviors before designing English courses to maintain positive attitudes toward English and English language learning. Overall, the students showed a positive attitude towards English. The questionnaire's results also showed that respondents recognized English's relevance in this time period. These are shown by their feeling, beliefs, or activities towards English.